If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 15)(x + 17) = 0 Reorder the terms: (15 + x)(x + 17) = 0 Reorder the terms: (15 + x)(17 + x) = 0 Multiply (15 + x) * (17 + x) (15(17 + x) + x(17 + x)) = 0 ((17 * 15 + x * 15) + x(17 + x)) = 0 ((255 + 15x) + x(17 + x)) = 0 (255 + 15x + (17 * x + x * x)) = 0 (255 + 15x + (17x + x2)) = 0 Combine like terms: 15x + 17x = 32x (255 + 32x + x2) = 0 Solving 255 + 32x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (17 + x)(15 + x) = 0Subproblem 1
Set the factor '(17 + x)' equal to zero and attempt to solve: Simplifying 17 + x = 0 Solving 17 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + x = 0 + -17 x = 0 + -17 Combine like terms: 0 + -17 = -17 x = -17 Simplifying x = -17Subproblem 2
Set the factor '(15 + x)' equal to zero and attempt to solve: Simplifying 15 + x = 0 Solving 15 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + x = 0 + -15 x = 0 + -15 Combine like terms: 0 + -15 = -15 x = -15 Simplifying x = -15Solution
x = {-17, -15}
| 6x^2-18=7x | | -4(w+9)=5w+9 | | 11n-9n+3n-4n=14 | | 5(x+5)-7x=33 | | 7b−2/5=6b−7/5 | | x^2-8x-82=2 | | 11x=1260+5x | | 4x^2/8x | | s+18000=7500 | | 3y^6/9z^4 | | 7x=1225 | | y=-18+4 | | -94=4-7x | | 19w-5w-10w=16 | | 3(1+8n)-6=-24+3n | | 9u-5u+2u-3u-u=20 | | cot(x)=(-1.7) | | -40+6n=5(1+3n) | | 2(v-9)-2=-4(-5v+9)-8v | | s-18000=7500 | | w^2-15w+36=0 | | 36=(60/360)*x*x | | 2cos^2(x)tan(x)-tan(x)=0 | | -6v+2=-2(v-5) | | 7h-6h=15 | | 6(w-7)-8w=-36 | | 10h-7h=18 | | 13h+7h=20 | | s-7500=18000 | | 7x+25+3x=16-2x-3 | | 8m+2=9m+4 | | 4v+3-3(-5v-1)=5(v-2) |